Effects of temperature and hold time on dynamic strain aging in a nickel based superalloy. (August 2014) - Cornet, C.; Wackermann, K.; Stöcker, C.; Christ, H-J.; Lupton, C.; Hardy, M.; Tong, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Serrations known as Portevin Le-Chatelier effect have been observed in a coarse grained nickel based superalloy RR1000 in the temperature range from 300 to 750°C. These serrations may be due to dynamic strain aging (DSA), which affects the stress relaxation behaviour of the material. Further experiments have been carried out over a wide range of temperature and under selected loading conditions to interrogate the DSA phenomenon. The results show that, in addition to serrations, the alloy also exhibits unusual strain rate insensitivity and increased strain hardening in the DSA temperature regime. Possible mechanisms of DSA have been explored using transmission electron microscopy (TEM) to examine typical samples tested under selected and well defined loading conditions.